(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
The present contribution addresses the question of attribution of private conduct to international organizations, more specifically whether the conduct of private military and security companies can be equated with that of the European Union in connection with migration and border control. The paper also incorporates the analysis of two contracts concluded between a private company and the European Asylum Support Office for provision of security services for the premises of the institution and for hotspots in Greece. The main findings of the paper are that while there are a number of ways to attribute the conduct of private entities to international organizations such as exercising elements of governmental authority or effective control over specific operations of private persons, there are inherent difficulties within the procedural aspects of proving such an attributional link. In addition to this, in spite of contrary scholarly opinion, this paper asserts that private military and security companies do not play a significant role in implementing the European Agenda on Migration, at least on the EU level. Conversely, the services they provide are not unique to migration control, but necessary for the effective operation of EASO. The attribution of the examined conduct is not possible through exercising elements of governmental authority, and proving effective control for a specific operation would also encounter considerable difficulties.